2018
DOI: 10.1186/s12891-018-2171-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and under-diagnosis of vertebral fractures on chest radiograph

Abstract: BackgroundVertebral fracture is the most common fragility fracture but it remains frequently unrecognized and is underdiagnosed worldwide. In this retrospective study, we examined the prevalence of moderate and severe vertebral fractures on chest radiographs of hospitalized female patients aged 50 years and older and determined missed diagnosis of vertebral fractures in the original radiology reports.Methods3216 female patients 50 years of age and older were enrolled in our study. The patients’ medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
1
32
2
Order By: Relevance
“…Vertebral fractures, in particular, are seldom noted in medical records and reports and, if they are mentioned, are often reported with ambiguous or confusing terminology. (34)(35)(36)(37)(38) Additionally, patients are at highest risk for another fracture in the months immediately after the initial hip or vertebral fracture, (39) and steps need to be taken on an urgent basis to reduce that risk. When unable to determine whether the patient's usual health care provider has been notified, sufficient action might entail calling the provider or sending an email or letter.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
“…Vertebral fractures, in particular, are seldom noted in medical records and reports and, if they are mentioned, are often reported with ambiguous or confusing terminology. (34)(35)(36)(37)(38) Additionally, patients are at highest risk for another fracture in the months immediately after the initial hip or vertebral fracture, (39) and steps need to be taken on an urgent basis to reduce that risk. When unable to determine whether the patient's usual health care provider has been notified, sufficient action might entail calling the provider or sending an email or letter.…”
Section: Fundamental Recommendations and Rationalesmentioning
confidence: 99%
“…Similarly undiagnosed vertebral fractures have been reported in 9.2% (259) patients following retrospective review of routine 3216 chest radiographs. The prevalence of vertebral fracture was 2.4% in women aged 50-59 years and it increased to 8.9% in women aged 60-69 years and to 21.9% in women aged ≥70 years [20].…”
Section: Discussionmentioning
confidence: 92%
“…A diagnosis of OP or previous fragility fracture was reported in around one-third of patients by Ong et al Most patients (75% men and 78% women) had five or more co-pathologies and many of them were more dependent with activities of daily living on discharge compared to their pre-admission level [8]. The incidence of new VCF in female and male aged 50 years and over was 10.7/1000 person years and 5.7/1000 person years respectively, and the prevalence increased from 3% in females under 60 years of age to 20% in females aged over 70 years, and from 7.5 to 20% in males over the same age range [9].…”
Section: Epidemiologymentioning
confidence: 88%
“…In spite of the fact that, BMD assay is considered the best predictor of osteoporotic fragility fracture risks, it is always recommended to perform adequate clinical evaluation [12].Jager et al showed that, combined vertebral fracture assessment (VFA) and BMD method detects previously unknown VCF's in nearly one out of each six patients, with significant impact on management[7]. Radiology-Vertebral compression fractures need radiological confirmation (semiquantitative method of Genant by the conventional spine radiography is traditionally used in the evaluation of VCF's), but are often undiagnosed by radiologists, with a misdiagnosis rate up to 50%[9]. Reasons for this inadequacy are; 1-Vertebral compression fractures frequently do not present as a clinically recognizable event.…”
mentioning
confidence: 99%